2004
DOI: 10.1094/pdis.2004.88.8.858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reduced Tillage, Resistant Cultivars, and Reduced Fungicide Inputs on Progress of Early Leaf Spot of Peanut (Arachis hypogaea)

Abstract: Field experiments were conducted in 2000 and 2001 on Georgia Green, Florida MDR-98, and C-99R peanut (Arachis hypogaea) cultivars in Tifton, GA, to determine the effects of tillage practices on early leaf spot (Cercospora arachidicola) epidemics under standard fungicide regimes and fungicide regimes with fewer applications. Leaf spot epidemics were suppressed in reduced tillage (strip-till) plots compared with conventional tillage plots and were suppressed in MDR-98 and C-99R cultivars compared with the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 21 publications
10
38
0
1
Order By: Relevance
“…Due to slightly higher disease tolerance compared to Bailey, good agronomic characteristics, high yield and quality under a variety of growing environments, and the presence of the high-oleic trait, Sullivan is an excellent cultivar for Virginiatype peanut production in the Virginia-Carolina region. A lack of yield response to higher-input fungicide programs for Sullivan and Bailey demonstrates the value of incorporating disease resistance/tolerance in peanut breeding programs (Wynne et al, 1991;Monfort et al, 2004;Cantonwine et al, 2006;Chapin et al, 2010). Furthermore, high yields and net returns of Sullivan regardless of fungicide program suggests further reducing fungicide inputs during production of this and other disease resistant/tolerant cultivars may be possible under low to moderate disease pressures as suggested by previous studies (Phipps, 1993;Cantonwine et al, 2006;Woodward et al, 2010Woodward et al, , 2014.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Due to slightly higher disease tolerance compared to Bailey, good agronomic characteristics, high yield and quality under a variety of growing environments, and the presence of the high-oleic trait, Sullivan is an excellent cultivar for Virginiatype peanut production in the Virginia-Carolina region. A lack of yield response to higher-input fungicide programs for Sullivan and Bailey demonstrates the value of incorporating disease resistance/tolerance in peanut breeding programs (Wynne et al, 1991;Monfort et al, 2004;Cantonwine et al, 2006;Chapin et al, 2010). Furthermore, high yields and net returns of Sullivan regardless of fungicide program suggests further reducing fungicide inputs during production of this and other disease resistant/tolerant cultivars may be possible under low to moderate disease pressures as suggested by previous studies (Phipps, 1993;Cantonwine et al, 2006;Woodward et al, 2010Woodward et al, , 2014.…”
Section: Resultsmentioning
confidence: 59%
“…As new cultivars with partial disease resistance are developed and released, the need for costly fungicide inputs to produce acceptable yields has decreased (Monfort et al, 2004;Cantonwine et al, 2006). The Virginia-type cultivar Bailey was released in 2011 (Isleib et al, 2011), and the partial resistance of this cultivar to diseases including late leaf spot, CBR, and Sclerotinia blight, as well as good yield and quality characteristics, has made this the cultivar of choice for growers in the Virginia-Carolina region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While not always increasing yield, the benefit through changes in insects populations (Olson et al, 2006), weed species shift and pressure Price et al, 2007), and reduced disease pressures (Monfort et al, 2004;Wright and Porter, 1991b) illustrates that producers will seek conservation systems to fill specific needs in their cropping systems. This is evident in adoption rates of conservation tillage which stands around 30% (J. Beasley, personnel communication) in the SE U.S. A linkage to increased water use efficiency could increase adoption of conservation tillage in peanut, but perhaps more importantly provide non-irrigated growers a risk mitigation tool not previously considered.…”
mentioning
confidence: 99%
“…Oklahoma producers have increased their adoption of strip tillage (ST) and NT systems in peanut production as a means of reducing costs and conserving soil resources, but the literature contains mixed reports on the effect of conservation tillage on disease and yield (Grichar andBoswell, 1987, Jordan et al, 2003;Monfort et al, 2004). Monfort et al (2004) observed that reduced tillage practices, like ST, may help with foliar disease management in peanut, especially when ST is used in combination with moderately resistant cultivars. They observed a delay in leaf spot development with reduced tillage.…”
mentioning
confidence: 99%